EKSTRAKSI GELATIN KEPALA IKAN KURISI (Nemipterus bathybius) DENGAN PERLAKUAN ASAM - Ulfatul Mardiyah (Samakia : Jurnal Ilmu Perikanan, 2017)
Gelatin is one type of protein degradation of triple helix collagen structure with the aid of acid and heat. Fish gelatin is very potential to be used as alternative gelatin substitute gelatin of cow or pig. The objective of this research was to utilize fish curry head as processed gelatin source using hydrochloric acid (HCl) 2,98% with extraction temperature 74 oC and extraction time 5,42 hours and gelatin production result compared with commercial gelatin. The yield of gelatin is 4.92%. characteristic pink perch gelatin are water content 8.23%, ash content 0.85%, protein content 88.54%, fat content 0.13%, gel strength 311,01 g.bloom, viscosity 5 cP, pH 5.43, gel temperature 10,12 oC and melting temperature 20,37 oC. Based on t-test, the physicochemical characteristics generated by the gelatin of pink perch head are generally lower than that of commercial gelatin.